An investigation into the effect of potential modifiers on the flotation of a copper sulphide ore - Dzinza, Lucia (Department of Chemical Engineering, 2019)
Oxidation, adsorption and reduction reactions are electrochemical in nature in the flotation of sulphide minerals which have semiconducting properties. Electrochemical mechanisms have two valuable implications in flotation, the potential across the mineral/solution interface determines flotation recovery and the anodic oxidation reaction involving the collector is an important parameter in imparting floatability. The reactions are dependent on the redox conditions in the pulp phase. Chemical control of redox potential (Eh) using potential modifiers may be exploited in flotation processes of sulphide minerals to improve their floatability, recoveries and grades; owing to the formation of a hydrophobic dithiolate or metal thiolate in the case of thiol collectors. In addition, chemical control of Eh is advantageous as it renders a more uniform electrochemical environment around the sulphide particles as compared to the external control of pulp potential. The adjustment of pulp potential using potential modifiers is being exploited as one of the main control parameters in sulphide flotation studies as it provides a diagnostic tool to develop flotation strategies and alleviate flotation challenges. Though potential modifiers have been previously investigated, no literature has addressed the correlation between their flotation performances on copper sulphides to their respective rest potentials at different concentrations. The present study explored the use of potential modifiers such as sodium hypochlorite (NaClO), potassium permanganate (KMnO₄) and potassium dichromate (K₂Cr₂O₇) on the flotation of a copper sulphide ore from Kansanshi Copper mine in Zambia. The potential modifiers were investigated at 1x10⁻⁴, 1x10⁻³ and 1x10⁻² mols which gave rise to various Eh values for each modifier. Batch flotation and froth stability tests were carried out at the ore’s natural pH whilst varying Eh. The dynamic stability factor (Σ) was used to quantify froth stability. Electrochemical techniques have been considered as an appropriate approach in the study of collector-mineral interactions. To complement results obtained from batch flotation and froth stability tests, rest potential measurements were carried out to determine the characteristic species formed on the chalcopyrite mineral surface at specific conditions. The potential modifier-collector-mineral interactions were investigated through rest potential measurements using the aforementioned potential modifiers, a thiol collector sodium iso-butyl xanthate (SIBX) and a pure chalcopyrite mineral. It was hypothesized that assuming an X⁻/X₂ equilibrium potential below 100 mV for SIBX, a redox potential range of 100-400 mV promotes good copper floatability due to the formation of dixanthogen and thus hydrophobic mineral particles which would result in a moderately stable froth. Rest potentials above 500 mV were hypothesized to reduce copper floatability due to the presence of very hydrophobic mineral particles, which would increase bubble coalescence and bubble breakage or result in highly stable froth. In this study, the equilibrium potential of SIBX at 6.24x10⁻⁴ M was measured to be 80 mV. Furthermore, equilibrium potential of SIBX was determined to be concentration dependent. Rest potential measurements for all conditions investigated were in excess of the measured equilibrium potential, therefore implying that the dixanthogen species was formed as postulated. It was found that an increase in concentration of potential modifiers increased froth stability or bubble coalescence depending on the potential modifier used. Furthermore, concentrations of potential modifiers resulting in Eh values of 137-476 mV resulted in high copper recoveries >88%, with 1x10⁻² mols of KMnO₄ at 540 mV giving a very low copper recovery of 4.8%. However, though high copper recoveries were obtained between concentrations that gave rise to an Eh range of 137-476 mV, a slight decrease in copper recoveries of approximately <4%, was observed with even larger increases in concentrations of potential modifiers. The findings of this study showed that the use of potential modifiers improved copper grades as a result of the reduction in gangue material recovery. In addition, the present study has shown that though concentration or Eh induced by potential modifiers may affect the flotation performance of sulphide ores, the most dominant factor that has shown to have a greater impact is the nature of the potential modifier. Comparing the findings of this work to literature findings for NaClO, it was determined that different sulphide minerals indeed exhibit different rates of redox reactions at given conditions. Ultimately, an inverse relationship was determined to exist between copper recoveries and rest potential measurements. This study has provided insight into the use of potential modifiers in the flotation of copper sulphides from an electrochemical perspective.